ТЕКТОНИКА И ИСТОРИЯ РАЗВИТИЯ ЮГО-ВОСТОЧНЫХ РАЙОНОВ ЗАПАДНОЙ СИБИРИ В МЕЗОЗОЕ И КАЙНОЗОЕ - Конторович В.А. (My University, 2002)
Выполнен анализ истории тектонического развития юго-восточных районов Западной Сибири в мезозойский и кайнозойский периоды и дана характеристика современной тектоники осадочного чехла этого региона. Основой для исследований служили региональные структурные карты М 1:500000 и региональные временные разрезы, построенные с учетом всей геолого-геофизической информации, полученной геологами и геофизиками за полувековую историю изучения региона. В рамках исследований решены следующие задачи: на современном информационном уровне создан набор электронных структурных карт и карт изопахит; обобщены предложения различных исследователей, проведен статистический анализ данных по площадям структур и сформулированы предложения по уточнению критериев классификации тектонических элементов применительно к молодым платформенным областям; построена новая версия схемы тектоники юрского структурного яруса юго-восточных районов Западной Сибири; осуществлен анализ истории тектонического развития исследуемой территории в мезозойскую и кайнозойскую эры, установлены основные этапы образования структур; выделены периоды наибольшей тектонической активности, сопровождающиеся формированием разрывных нарушений.

This work presents the analysis of tectonic history of the southeastern regions of West Siberia in the Mesozoic and Cenozoic as well as the characterization of the present-day tectonic structure of the sedimentary cover of this region. The basis for carrying out-these investigations were the regional structural maps of scale 1: 500000 and regional time sections constructed with regard for all geologicgeophysical information acquired by geologists and geophysicists during the half-century history of the region studies.. Within the framework of the performed studies, the following problems have been solved: a set of electronic structural maps and isopach maps was constructed at the modern information level; proposals made by various investigators were generalized, statistical analysis of data on structure areas was performed, and proposals for refining the criteria of classification of tectonic elements as applied to young platform districts were formulated; a new version of the scheme of tectonic structure of the Jurassic structural stage was developed for the southeastern areas of West Siberia; the tectonic history of the studied area in the mesozoic and cenozoic was analyzed, and the major stages of the structure formation were identified; the periods of the most intense tectonic activity accompanied by formation of faults were recognized.
Keywords: Cenozoic; Mesozoic; Jurassic; 551.24(571.1); Cenozoic; Кайнозой; Mesozoic; Мезозой; Мезозой::Юрская; Mesozoic::Jurassic